Sex- and Disease-Specific Inflammasome Signatures in Circulating Blood Leukocytes of Patients with Abdominal Aortic Aneurysm - Xiaoyu Wu; Sinan Cakmak; Markus Wortmann; Maani Hakimi; Jian Zhang; Dittmar Böckler; Susanne Dihlmann (BMC, 2016)
Abstract Male sex is a risk factor for abdominal aortic aneurysm (AAA). Within the AAA adventitia, infiltrating leukocytes express high levels of inflammasome components. To further elucidate the role of inflammatory cells in the pathogenesis of AAA, we here addressed expression and functionality of inflammasome components in peripheral blood mononuclear cells (PBMC) of AAA patients in association with sex. PBMC and plasma were isolated from 100 vascular patients, including 34 pairs of AAA patients and age/sex-matched non-AAA patients. Male PBMC were found to express significantly higher mRNA levels of AIM2, NLRP3, ASC (PYCARD), CASP1, CASP5, and IL1B (all P < 0.0001) than female PBMC. Within the male patients, PBMC of AAA patients displayed increased mRNA levels of NLRP3 (P = 0.044), CASP1 (P = 0.032) and IL1B (P = 0.0004) compared with matched non-AAA PBMC, whereas there was no difference between female AAA and non-AAA patients. The relative protein level of NLRP3 was significantly lower in PBMC lysates from all AAA patients than in matched controls (P = 0.038), whereas AIM2 and active Caspase-1 (p10) protein levels were significantly increased (P = 0.014 and P = 0.049). ELISA revealed significantly increased IL-1α (mean = 6.34 versus 0.01 pg/mL) and IL-1β plasma levels (mean = 12.07 versus 0.04 pg/mL) in AAA patients. The data indicate that male PBMC display a systemic proinflammatory state with primed inflammasomes that may contribute to AAA-pathogenesis. The AAA-specific inflammasome activation pattern suggests differential regulation of the sensors AIM2 and NLRP3 in inflammatory cells of AAA patients.